Beyond Empire and Nation; The Decolonization of African and Asian societies, 1930s-1960s - Raben, Remco; Bogaerts, Els (2012)
The decolonization of countries in Asia and Africa is one of the momentous events in the twentieth century. But did the shift to independence indeed affect the lives of the people in such a dramatic way as the political events suggest? The authors in this volume look beyond the political interpretations of decolonization and address the issue of social and economic reorientations which were necessitated or caused by the end of colonial rule. The book covers three major issues: public security; the changes in the urban environment, and the reorientation of the economies. Most articles search for comparisons transcending the colonial and national borders and adopt a time frame extending from the late colonial period to the early decades of independence in Asia and Africa (1930s-1970s).The volume is part of the research programme ‘Indonesia across Orders’ of the Netherlands Institute for War Documentation.Contributors to the volume are: Greg Bankoff, Raymond Betts, Ann Booth, Cathérine Coquéry-Vidrovitch, Freek Colombijn, Frederick Cooper, Bill Freund, Karl Hack, Jim Masselos and Willem Wolters.